N-Acetyl-seryl-aspartyl-lysyl-proline Alleviates Renal Fibrosis Induced by Unilateral Ureteric Obstruction in BALB/C Mice - Gary C. W. Chan; Wai Han Yiu; Hao Jia Wu; Dickson W. L. Wong; Miao Lin; Xiao Ru Huang; Hui Yao Lan; Sydney C. W. Tang (Mediators of Inflammation)
To expand the armamentarium of treatment for chronic kidney disease (CKD), we explored the utility of boosting endogenously synthesized N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP), which is augmented by inhibition of the angiotensin converting enzyme. Male BALB/c mice underwent unilateral ureteral ligation (UUO) or sham operation and received exogenously administered Ac-SDKP delivered via a subcutaneous osmotic minipump or Captopril treatment by oral gavage. Seven days after UUO, there were significant reductions in the expression of both collagen 1 and collagen 3 in kidneys treated with Ac-SDKP or Captopril, and there was a trend towards reductions in collagen IV, α-SMA, and MCP-1 versus control. However, no significant attenuation of interstitial injury or macrophage infiltration was observed. These findings are in contrary to observations in other models and underscore the fact that a longer treatment time frame may be required to yield anti-inflammatory effects in BALB/c mice treated with Ac-SDKP compared to untreated mice. Finding an effective treatment regimen for CKD requires fine-tuning of pharmacologic protocols.